1999
DOI: 10.1073/pnas.96.13.7244
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven motor in the outer hair cell: Effect of a mechanical constraint

Abstract: The outer hair cell has a unique voltagedependent motility associated with charge transfer across the plasma membrane. To examine mechanical changes in the membrane that are coupled with such charge movements, we digested the undercoating of the membrane with trypsin. We inf lated the cell into a sphere and constrained the surface area by not allowing volume changes. We found that this constraint on the membrane area sharply reduced motor-associated charge movement across the membrane, demonstrating that charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 22 publications
8
36
1
Order By: Relevance
“…5G. If the diameter of monomeric prestin in the membrane were estimated to be 5ϳ7 nm as expected from the diameter of a potentially tetrameric prestin complex observed in the lateral membrane of OHCs (10ϳ14 nm (28)), the total unitary displacement of a single prestin molecule (0.20 ϩ 0.34) nm is expected to change the membrane area 3ϳ4 nm 2 , which agrees with the estimates by others (2ϳ4 nm 2 (29,30)). …”
Section: Twosupporting
confidence: 87%
“…5G. If the diameter of monomeric prestin in the membrane were estimated to be 5ϳ7 nm as expected from the diameter of a potentially tetrameric prestin complex observed in the lateral membrane of OHCs (10ϳ14 nm (28)), the total unitary displacement of a single prestin molecule (0.20 ϩ 0.34) nm is expected to change the membrane area 3ϳ4 nm 2 , which agrees with the estimates by others (2ϳ4 nm 2 (29,30)). …”
Section: Twosupporting
confidence: 87%
“…This phenomenon may play a role in reducing mechanically generated gating currents when the cell is collapsed from its cylindrical shape; however, from our data it appears that mechanically evoked gating currents are reduced in a graded fashion as intracellular pressure is decreased. Even more confounding is the observation that Q max derived from voltage stimulation appears to decrease as intracellular pressure is increased [14,22] until, under extreme conditions, charge movement can be blocked substantially [1]. Of course, these findings might suggest an opposite result from what we found.…”
Section: Discussionmentioning
confidence: 55%
“…We noted that motor sensitivity to membrane stress appeared greater after cortical cytoskeleton destruction with trypsin [14]. Adachi and Iwasa [1] quantified this sensitivity change by degree of V pkcm shift, and found that sensitivity was about six times greater than normal, i.e., 155 mV/kPa compared to normal whole cell values of 25 mV/kPa [2,14], which may account for their observed step-like C m decrease [1]. Our present data may provide an alternative explanation for the effects of stress on the whole cell as opposed to patch nonlinear capacitance.…”
Section: Discussionmentioning
confidence: 70%
“…It has been argued that changes in peak C m arise from membrane tension working through an anisotropic cytoskeleton or working on an anisotropic motor [9,13]; indeed, isolated patch recordings, where tension can be applied isotropically, show only a shift in V pkcm [9,16]. Nevertheless, even in OHCs that have become spherical due to intracellular trypsin treatment, and where applied tension should be isotropic, peak C m is altered by turgor pressure [1,14]. We noted that motor sensitivity to membrane stress appeared greater after cortical cytoskeleton destruction with trypsin [14].…”
Section: Discussionmentioning
confidence: 99%